(untitled) (Research, Society and Development, 2022)
A Regional Innovation System is characterized by the integrated action between its actors: companies, universities, research institutes, Technology Transfer offices and public and private financing agents in order to facilitate innovations at a regional level. Considering that the university is the main knowledge-producing agent within the context of Innovation Systems, the present research has the general goal of mapping of the innovation generated in Higher Education Institutions headquartered in the cities of the Midwest region of Minas Gerais. To this end, a semi-structured questionnaire was applied to the NITs managers or to the person indicated by the participating institutions campuses directors. Eleven Higher Education Institutions based in cities in the Midwest region of Minas Gerais participated in the research, five of which were federal institute campuses, three public university campuses and three private university campuses. All the questions were related to the innovation generated only on the campuses located in the Midwest region of Minas Gerais and not in the institution as a whole and had as themes the Intellectual Property, Technology Transfer and incentive to Entrepreneurship. The results demonstrated the potential to support innovation by most of the researched HEIs, which for the most part have protected intellectual properties and carry out activities to support Entrepreneurship. However, the small number of Technology Transfers to the productive sector, demonstrates the need to improve the relationship with companies in the region. For this, an important action would be the implementation of NIT on the region’s campuses.